KARAKTERISTIK LOKASI PASAR TRADISIONAL DAN DAMPAK OPERASIONALNYA : STUDI KASUS KOTA SEMARANG - Rasinanda Muhammad Rizal; Nur Rahman Alhamidi; Ferry Hermawan; Ismiyati Ismiyati (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2018)
Traditional market is the place which represents the transaction between sellers and buyers. However, by the development of the period rapidly, the existence of traditional market begins to be threatened. It is because the proliferation of retail business from foreign funds, for example is Minimarket. Due to the proliferation of the Minimarket, people has been prefer to visit Minimarket rather than traditional market. Clean place and free from the word of dirty have made visitors more comfortable to visit Minimarket. And this condition is in opposite with the traditional market which seems slum, muddy and far from hygienic. This situation has succesfully made the traditional market left behind of the modern market. This research aims to know the characteristic of location of the traditional market and its operational impact and recommend the traditional market model. The model of market location can enhance the competitiveness of traditional market with modern markets. As for which becomes the object of this research are, traditional market data that listed in the Market Service of Semarang city, that market conditions are obtained by means of direct observation or interviews to the merchant market, the market manager and the buyer's market. As for the secondary data used is DED of market, the number of market stalls, number of floor los data, data number of traders, market land area data, and data market building area. The conclusions of this research was obtained some variables from location factors that affect the success of the revitalization, covering a distance of main street market, broad visibility, parking lots, the amount of market traders, the number of entry to the market, and the number of transport towards the market. As for the success of the revitalization of the market was also influenced by his market in the populous region. Because there is still no recommendations placement location a strategic market, for it is this research make a model of market location recommendations and a population density of traditional market.